An analysis of strategic factors hindering the performance of small and medium industries in textile in Dar-Es-Salaam: Case study of Friendship Textile Company Ltd. (FTC) - Msemo, Daud H (2024)
A dissertation report submitted to the School of Business in partial fulfillment of the requirements of Mzumbe University‟s Masters Degree in Accounting and Finance